(untitled) (International Seven Journal of Multidisciplinary, 2026)
Menopause is a physiological milestone characterized by the loss of ovarian follicular activity, often associated with vasomotor symptoms (VMS) and genitourinary syndrome of menopause (GSM). Although Menopausal Hormone Therapy (MHT) is the most effective intervention for symptomatic relief and prevention of bone loss, its use is limited by contraindications in specific subgroups, such as breast cancer survivors and patients with a history of endometriosis, requiring individualized approaches. Diagnosis is clinical and retrospective, but Anti-Müllerian Hormone (AMH) is a sensitive biomarker of ovarian reserve, useful in predicting impending menopause, despite persistent inaccuracy in determining the exact timing. Advances in non-hormonal alternatives represent a promising frontier, including neurokinin receptor antagonists such as fezolinetant and elinzanetant for VMS, and topical therapies such as vaginal hyaluronic acid and laser (CO2 and Er:YAG) for GSM/vulvovaginal atrophy, which demonstrate comparable efficacy in patient-centered outcomes, with favorable safety profiles for patients at oncologic risk. In addition, MHT has been shown to optimize weight loss response when combined with GLP-1 agonists such as semaglutide. However, therapeutic management of menopause still lacks long-term data regarding the cardiovascular, skeletal, and oncologic safety of new non-hormonal therapies, reinforcing the need for prospective studies to consolidate safe and individualized strategies during the climacteric period.